2017
DOI: 10.1002/bjs.10485
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional observational study of the availability of evidence supporting novel implantable devices used in gastrointestinal surgery

Abstract: Only one in ten novel implantable devices available for use in gastrointestinal surgical practice is supported by high-quality RCT evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Similar reviews have been performed in orthopaedics 37 and gastrointestinal surgery. 3 Findings were similar, although these studies did not look at the quality (in terms of risk of bias) of the RCTs, only whether there were any. The evidence in this study for vascular implantable devices adds to this body of literature and has the same obvious conclusions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar reviews have been performed in orthopaedics 37 and gastrointestinal surgery. 3 Findings were similar, although these studies did not look at the quality (in terms of risk of bias) of the RCTs, only whether there were any. The evidence in this study for vascular implantable devices adds to this body of literature and has the same obvious conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…There are currently over 80 of these bodies. 3,4 The evaluation procedures and outcomes are protected by commercial confidentiality. Consequently, none disclose the evidence provided for the decision making process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other issues identified included a poorly described clinical indication or target population [ 32 ]; the use of predicate devices [ 24 , 26 ]; small sample sizes [ 30 , 31 ]; no patient-relevant study outcomes [ 10 , 17 , 28 ]; or the sole use of surrogate outcomes [ 28 ]; and limited long-term data [ 26 ]. No evidence was found for some devices [ 33 , 34 , 29 ], whilst some authors found that the evidence for some devices showed them to be no better or less safe/effective than other treatments [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sauerland et al (2014) warn that all the steps in the IDEAL framework need to be taken [ 18 ], including conducting RCTs to determine efficacy: “The pitfall to be avoided is acceptance of preliminary non-randomized data as proof of the new devices or procedure’s superiority.” This stepwise approach to introducing high-risk devices whilst gathering additional robust RCT data on their effectiveness and longer-term safety profile is another potential way of preventing the widespread adoption of unproven treatments. However, this requires the support of the regulatory system [ 29 ] to limit the risk of harm [ 56 , 57 ]. Additional legislation may be required to allow only limited market access until this data is available and to require special reporting of all clinical outcomes post-CE marking.…”
Section: Discussionmentioning
confidence: 99%